Association between SARS-CoV-2 gene specific Ct values and COVID-19 associated in-hospital mortality - Sikhosana, Mpho L.; Welch, Richard; Musekiwa, Alfred; Makatini, Zinhle; Ebonwu, Joy; Blumberg, Lucille; Jassat, Waasila (Frontiers in Epidemiology, 2024)
Background: Since there are currently no specific SARS-CoV-2 prognostic viral biomarkers for predicting disease severity, there has been interest in using SARS-CoV-2 polymerase chain reaction (PCR) cycle-threshold (Ct) values to predict disease progression Objective: This study assessed the association between in-hospital mortality of hospitalized COVID-19 cases and Ct-values of gene targets specific to SARS-CoV-2. Methods: Clinical data of hospitalized COVID-19 cases from Gauteng Province from April 2020-July 2022 were obtained from a national surveillance system and linked to laboratory data. The study period was divided into pandemic waves: Asp614Gly/wave1(7 June-22 Aug 2020); beta/wave2(15 Nov 2020-6 Feb 2021); delta/wave3(9 May-18 Sept 2021) and omicron/wave4(21 Nov 2021-22 Jan 2022). Ct-value data of genes specific to SARS-CoV-2 according to testing platforms (Roche-ORF gene; GeneXpert-N2 gene; Abbott-RdRp gene) were categorized as low (Ct<20), mid (Ct20-30) or high (Ct>30). Results: There were 1205 recorded cases: 836(69.4%;wave1), 122(10.1%;wave2) 21(1.7%; wave3) and 11(0.9%;in wave4). The cases’ mean age(+SD) was 49 years(+18), and 662(54.9%) were female. There were 296(24.6%) deaths recorded: 241(81.4%;wave1), 27(9.1%;wave2), 6(2%;wave3), and 2(0.7%;wave4) (p<0.001). Sample distribution by testing platforms was: Roche 1033(85.7%), GeneXpert 169(14%) and Abbott 3(0.3%). The median(IQR) Ct-values according to testing platform were: Roche 26(22-30), GeneXpert 38(36-40) and Abbott 21(16-24). After adjusting for sex, age and presence of a comorbidity, the odds of COVID-19 associated death were high amongst patients with Ct values 20-30(adjusted Odds Ratio [aOR]2.25; 95%CI1.60-3.18) and highest amongst cases with Ct-values <20(aOR 3.18; 95%CI1.92-5.27), compared to cases with Ct-values >30. Conclusion: Although odds of COVID19-related death were high amongst cases with Ct-values <30, Ct values were not comparable across different testing platforms, thus precluding the comparison of SARS-CoV-2 Ct-value results.